PERFORMANCE AND TIBIA CHARACTERISTICS OF BROILERS FED DIETS CONTAINING RAW OR TREATED OAK ACORN (QUERCUS BRANTII LINDL) - L. Ghaedi; M. Houshmand; S. Parsaei (Journal of Animal and Plant Sciences, 2018)
Using a completely randomized design, a total of 360 one-day-old male and female broiler chicks were allocated to 6 experimental diets with four replicates (15 birds each), to evaluate the effects of raw or treated oak acorn (OA) on the performance and tibia characteristics of broilers. First diet was a corn-based diet (without OA) as the control, while other 5 diets contained 150 g/kg OA (raw or treated with distilled water, acetic acid, sodium hydrogen carbonate (Alkali) and traditional method). Birds were given starter and finisher diets from 1 to 21 and 22 to 42 d of age, respectively. The results indicated that all treatment methods significantly reduced the content of phenolic compounds. Dietary inclusion of raw OA had no deleterious effect on performance and tibia characteristics when compared to the control. Treatment with Alkali caused the highest overall body weight gain while traditional method resulted in worse performance compared to the raw OA. In conclusion, 150 g/kg raw OA could be included in broiler diets, without adverse effects on their performance or tibia characteristics. Chemical treatment, particularly using Alkali, has the potential to reduce the content of phenols and maybe improve the nutritional value of OA.
Keywords: Broiler; Oak acorn; Performance; Tibia characteristic; Treatment